2021
DOI: 10.1096/fj.202002287rr
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the ligand recognition and catalysis of the key aminobutanoyltransferase CntL in staphylopine biosynthesis

Abstract: Transition metals are indispensable nutrients for all cellular life and are frequently incorporated into metalloproteins to serve as essential cofactors. 1 The competition between pathogens and human cells for transition metals is an important component of the pathogenesis of infectious diseases, and hosts have developed a strategy known as "nutritional immunity" to restrict the pathogens from accessing essential transition metals to prevent microbial infection. 2 Bacteria have evolved various systems to subve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In the bacterial NAS-like protein Staphylococcus aureus CntL that comprises merely a core-NAS domain, Luo et al (38) identified a linker region between its N- and C-terminal domain which is capable of conformational alternation between the open and closed states of SaCntL. The authors suggest that this linker region could have pivotal roles in allowing substrate entry, substrate recognition, and catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the bacterial NAS-like protein Staphylococcus aureus CntL that comprises merely a core-NAS domain, Luo et al (38) identified a linker region between its N- and C-terminal domain which is capable of conformational alternation between the open and closed states of SaCntL. The authors suggest that this linker region could have pivotal roles in allowing substrate entry, substrate recognition, and catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…51 Both MtNAS and CntL possess a Rossmann fold MT C-terminal domain with a characteristic glycine-rich motif that binds SAM as the ACP donor. 45,51 An open to closed conformational change upon substrate binding was noted for CntL and involves the partially disordered interdomain linker in the CntL-SAM binary complex becoming an ordered a-helix in the CntL-MTA-xNA ternary complex. 51 The mechanism of CntL catalyzed ACP transfer is otherwise analogous to that of MtNAS.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…45,51 An open to closed conformational change upon substrate binding was noted for CntL and involves the partially disordered interdomain linker in the CntL-SAM binary complex becoming an ordered a-helix in the CntL-MTA-xNA ternary complex. 51 The mechanism of CntL catalyzed ACP transfer is otherwise analogous to that of MtNAS. In addition to NAS and CntL, many other NAS-like enzymes have been identied or proposed in the biosynthesis of structurally diverse metallophores with an amino group serving as the acceptor nucleophile, which underscores the importance of SAM-dependent ACP modication of metallophores in bacteria.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study confirmed that during the synthesis of staphylopine, CntL stereoselectively carries out the catalysis of D-histidine and not L-histidine. These findings provided critical structural and mechanistic insights into CntL for a better understanding of of nicotianamine-like metallophores biosynthesis and the discovery of inhibitors of this process [ 92 ]. Concerning CntA, responsible for the recognition and transport of diverse solutes, a study was performed to investigate the structural conformation upon staphylopine binding.…”
Section: Metallophores Produced By Staphylococcus Aureusmentioning
confidence: 99%